Transcriptomics of acute myeloid leukaemia core bone marrow biopsies reveals distinct therapy response‐specific osteo‐mesenchymal profiles. (10th November 2022) - Treaba, Diana O.; Bonal, Dennis M.; Chorzalska, Anna; Castillo‐Martin, Mireia; Oakes, Alissa; Pardo, Makayla; Petersen, Max; Schorl, Christoph; Hopkins, Kelsey; Melcher, Dean; Zhao, Ting C.; Liang, Olin; et al.
Summary: While the bone marrow (BM) microenvironment is significantly remodelled in acute myeloid leukaemia (AML), molecular insight into AML‐specific alterations in the microenvironment has been historically limited by the analysis of liquid marrow aspirates rather than core biopsies that contain solid‐phase BM stroma. We assessed the effect of anthracycline‐ and cytarabine‐based induction chemotherapy on both haematopoietic and non‐haematopoietic cells directly in core BM biopsies using RNA‐seq and histological analysis. We compared matched human core BM biopsies at diagnosis and 2 weeks after cytarabine‐ and anthracycline‐based induction therapy in responders (<5% blasts present after treatment) and non‐responders (≥5% blasts present after treatment). Our data indicated enrichment in vimentin ( VIM ), platelet‐derived growth factor receptor beta ( PDGFRB ) and Snail family transcriptional repressor 2 ( SNAI2 ) transcripts in responders, consistent with the reactivation of the mesenchymal population in the BM stroma. Enrichment of osteoblast maturation‐related transcripts of biglycan ( BGN ), osteopontin ( SPP1 ) and osteonectin ( SPARC ) was observed in non‐responders. To the best of our knowledge, this is the first report demonstrating distinct osteogenic and mesenchymal transcriptome profiles specific to AML response to induction chemotherapy assessed directly in core BM biopsies. Detailing treatment response‐specific alterations in the BM stroma may inform optimised therapeutic strategies for AML.